Photometry of a galactic field at l = 232°. b = -6°: The old open cluster Auner 1, The Norma-Cygnus spiral arm, and the signature of the warped galactic thick disk - Carraro, Giovanni (2007)
We perform a detailed photometric study of the stellar populations in a Galactic field at l = 232°, b = -6° in the Canis Major (CMa) constellation. We present the first U, B, V, I photometry of the old open cluster Auner 1 and determine it to be ≈3.25 Gyr old and to lie 8.9 kpc from the Sun. In the background of the cluster, at more than 9 kpc, we detect a young population most likely associated with the Norma-Cygnus spiral arm. Furthermore, we detect the signature of an older population and identify its turnoff and red giant branch. This population is found to have a mean age of 7 Gyr and a mean metallicity of Z = 0.006. We reconstruct the geometry of the stellar distribution and argue that this older population, often associated with the CMa "galaxy," in fact belongs to the warped old thin- and thick-disk components along this line of sight.